Beyond glycemic control: a holistic perspective on psychosocial support in outpatient diabetes management - Hao, Lin-na; Ma, Xiao-wei; Kang, Li-na; Wang, Yu-ying; Shi, Hong (Frontiers in Endocrinology, 2025)
Conventional outpatient diabetes management, which focuses mainly on biomedical measures like glycemic control, may be inadequate for achieving sustainable long-term health outcomes, especially among patients with co-occurring psychosocial challenges. Although these methods are physiologically important, they often ignore key psychosocial factors that greatly affect self-management, treatment adherence, and clinical results. Based on the biopsychosocial model, this article proposes a comprehensive care framework that includes structured psychosocial support as a core part of diabetes management. Strong evidence shows that psychosocial factors—such as diabetes-related distress, mental health conditions, and social determinants—directly influence glycemic control, quality of life, and complication rates. The article also points out structural weaknesses in current healthcare systems that prevent integrated care. In response, a coordinated, multi-level strategy is introduced. This includes systematic psychosocial screening, communication methods supported by evidence, digital health technologies, and personalized stepped-care interventions. Finally, we recommend systemic reforms in clinical practice, payment policies, and medical education to support a shift toward person-centered, biopsychosocial diabetes care. These changes are necessary to address the complex nature of diabetes and improve both health outcomes and patient well-being.